The influence of contractors service quality dimension on apartment developers loyalty: The mediating role of developer satisfaction - Setijanto, Augustinus; So, Idris Gautama; Alamsjah, Firdaus; Tjhin, Viany Utami (International Journal of Management and Sustainability, 2025)
The main direction of this research is to examine the influence of customer satisfaction of apartment developers as an intervening factor between reliability, assurance, tangibility, responsiveness, and empathy, and developer loyalty towards apartment contractors in Indonesia. The originality of this research lies in the analysis of the mediating role of customer satisfaction in the relationship between assurances, empathy, reliability, and responsiveness as dimensions of service quality with customer loyalty of apartment developers. The research employs a quantitative method with a structural equation modeling approach. The population of the study comprises apartment developers in Indonesia, with data collected through an online survey. The data collection process obtained 316 usable respondents. The data that has been collected and filtered was then investigated using a structured equation modelling-partial least square approach with SMARTPLS. The statistical tests revealed that developer satisfaction significantly bridges the assurances, empathy, reliability, and responsiveness with customer loyalty of apartment developers toward contractors. This study offers several managerial implications regarding strategies that contractors can implement to achieve loyalty from apartment developers in Indonesia.